ANALYSIS OF INSURANCE AGENT IN HAJJ & UMRAH TRIP - Ayesha; Lesti Febrianti; Leo Candra Pratama; Jordan Pandu Alam; Arsyil Azhim; Erwin Saputra (CV. Era Digital Nusantara, 2023)
Hajj and Umrah trips are important religious activities for Muslims. In carrying out this trip, many pilgrims choose to use the services of a travel insurance agent to provide financial protection and guarantees in unexpected situations. Therefore, it is important to carry out an analysis of the insurance agents involved in the Hajj and Umrah trips. In this writing, it uses the research method of library research by discussing the roles and obstacles that occur in Hajj and Umrah agents.